Linguistic Deviation in Literary Discourse: A Theoretical Review of Types, Functions, and Interpretive Potential - Uzakova, Aziza Kuatbaevna (The Lingua Spectrum, 2026)
This article presents a theoretical review of linguistic deviation as a category of stylistic analysis in literary discourse. It examines deviation not as an accidental violation of language norms, but as a purposeful artistic device through which literary texts become salient, expressive, and rich. The discussion clarifies the relation between deviation and norm, showing that deviant forms are perceived through contrast with expected linguistic patterns and function as marked elements within the text. Particular attention is given to the types of deviation, including lexical, semantic, phonological, grammatical, morphological, graphological, dialectal, register, and historical deviation. The article considers the connection between deviation, foregrounding, and interpretation, emphasizing that deviant forms slow down perception, guide reader attention, and stimulate meaning construction. A comparative perspective on poetry and prose demonstrates that deviation operates across genres, though with different degrees of concentration. The review concludes that linguistic deviation remains one of the most productive mechanisms through which literature transforms ordinary language into a significant medium.